İstanbul Üniversitesi Kütüphanesi Türkçe Yazmalar 739 Numarada kayıtlı Mecmû'a-yı Nezâyir (25b-50a) (inceleme-metin-çeviri) - Yurdakul, Rabia Nur (My University, 2019)
Bu tezde tek nüshası İstanbul Üniversitesi Türkçe Yazmalar Kitaplığı 739 numarada kayıtlı olan 16. yüzyılın sonu 17. yüzyılın başında derlendiğini tahmin ettiğimiz Mecmû’a-yı Nezâyir adlı 250 varaklık nazire mecmuasının 25b-50a varakları arasındaki 85 şairin sadece gazellerden meydana gelen 138 tane şiirinin çeviri yazı metni ve nesre çevirisi sunulup üzerinde kısa incelemeler ve değerlendirmeler yapılmıştır.

In this thesis statement, transcriptions and translations of 138 poems were presented with reviews and interpretation. These 138 poems are the solely the odes of the 85 poets of the literary work named “Mecmû’a-yı Nezâyir” which are situated in nr. 739 at İstanbul University Library and Documentation Department of Rare Books Library as a single copy. Relevant odes of the 138 poets are belonging to 25b-50a laminas out of 250 laminas of aforementioned nazire magazine. Subjected nazire magazine is assumed as, compiled at the end of the 16th century.
Keywords: İstanbul Üniversitesi Kütüphanesi; Magazine; Mecmua; Nazire; Poet; Poetry; Şair; Şiir Istanbul University; Turkish literature; Türk edebiyatı